Fast and low-cost fabrication of 1D hematite photoanode in pure water vapor and air atmosphere: Investigation the effect of the oxidation atmosphere on the PEC performance of the hematite photoanodes - SARIOĞLU, CEVAT; DEMİRCİ, SELİM (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, hematite photoanodes were successfully fabricated by thermal oxidation of the commercial cold-rolled steel at 500 degrees C in pure water vapor and air atmosphere. The crystal phase structure, surface morphology, and optical properties of the hematite photoanodes were characterized using an X-ray diffractometer (XRD), field emission scanning electron microscopy (FESEM) and UV-VIS spectrophotometer, respectively. The results showed that hematite photoanodes had high crystalline phase and the annealing atmosphere influenced the morphology of the hematite photoanodes. Moreover, nanowhisker and nanorod shaped nanostructures were observed on the substrate. The optical band gap values of the hematite photoanodes varied between 2.38 and 2.70 eV. Photoelectrochemical (PEC) studies of the hematite photoanodes were assessed in the 0.1 M NaOH electrolyte solution using the Mott-Schottky analysis and electrochemical impedance spectroscopy techniques. The PEC findings exhibited that the hematite photoanode annealed 15-min in water vapor had best PEC performance achieving photocurrent density 0.244 mA/cm(2) at 1.6 V vs. V-RHE and highest carrier density value (N-D = 1.15 x 10(21) cm(-3)). Furthermore, the photoanodes annealed in water vapor atmosphere revealed at least three times higher PEC performance than that of photoanodes annealed in air. Thermal oxidation method in water vapor is an efficient methods for fabrication of hematite photoanodes. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hematite; Thermal oxidation; Water vapor; Photoelectrochemical (PEC); Electrochemical impedance spectroscopy (EIS); ALPHA-FE2O3 NANOTUBE ARRAYS; IRON-OXIDE FILMS; THIN-FILMS; PHOTOELECTROCHEMICAL PERFORMANCE; OPTICAL-PROPERTIES; THERMAL-OXIDATION; DEPOSITION; GROWTH; DYE; PHOTOOXIDATION